2020
DOI: 10.1155/2020/4917924
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Characteristics of Soil Gas and Strong Seismic Hazard Potential in the Liupanshan Fault Zone (LPSFZ)

Abstract: Eight soil gas measurements were performed in the Liupanshan fault zone (LPSFZ) to observe the concentration and flux of soil gas radon (Rn) and CO2 in October 2017 and October 2018. By combining the historical strong earthquake background and modern seismic activity of the fault zone, the relation between the geochemical distribution characteristics of soil gas and the seismicity of the fault zone was studied herein. Furthermore, the strong seismic hazard potential of the fault zone was discussed. Results sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 44 publications
0
1
0
1
Order By: Relevance
“…The frequency of seismic activity has been significantly lower than that in the west of Lingwu since 1970. Studies of low gas anomalies in some active fault zones indicated that the high locking degree of the fault constrains the migration of soil gas, whereas the creeping fault with a low locking degree is more favorable for the discharge of gas from deeper layers up toward the surface (Yang et al, 2018;Zhou et al, 2020;Yang et al, 2021). Although gas concentrations are low in the southern segment of the YRF, according to the slip rate inversed by InSAR, there is ~6.8 km locking in the southern segment of the YRF (Zhang et al, 2020), which the risk of strong earthquakes has increased.…”
Section: Gas Migration and Seismic Hazardmentioning
confidence: 99%
“…The frequency of seismic activity has been significantly lower than that in the west of Lingwu since 1970. Studies of low gas anomalies in some active fault zones indicated that the high locking degree of the fault constrains the migration of soil gas, whereas the creeping fault with a low locking degree is more favorable for the discharge of gas from deeper layers up toward the surface (Yang et al, 2018;Zhou et al, 2020;Yang et al, 2021). Although gas concentrations are low in the southern segment of the YRF, according to the slip rate inversed by InSAR, there is ~6.8 km locking in the southern segment of the YRF (Zhang et al, 2020), which the risk of strong earthquakes has increased.…”
Section: Gas Migration and Seismic Hazardmentioning
confidence: 99%
“…Pada konsentrasi tinggi diatas ambang batas aman, gas beracun yang terhirup manusia dan/atau hewan dapat menyebabkan pingsan, kesulitan bernapas, dan detak jantung yang meningkat, pada kondisi paling parah, bahkan dapat menyebabkan kematian. Dalam pengukuran konsentrasi gas, dan menentukan ambang batas aman paparan gas beracun pada makuk hidup, dinyatakan dalam satuan Part per Milion (PPM), yang mana merupakan perbandingan massa jenis gas per satujuta bagian dari udara ambient [12] [13] [14]. Pada emisi gas beracun yang dihasilkan oleh aktivitas gunung berapi, dapat bervariasi jenis dan konsentrasi gas yang dihasilkan tergantung dari aktifitas magma dan komposisi batuan yang ada pada kawah aktif gunung api.…”
Section: Pembahasanunclassified